Effects of the addition of leucine on flavor and quality of sausage fermented by Lactobacillus fermentum YZU-06 and Staphylococcus saprophyticus CGMCC 3475 - Liu, Rui; Ma, Yong; Chen, Lei; Lu, Chenyan; Ge, Qingfeng; Wu, Mangang; Xi, Jun; Yu, Hai (Frontiers in Microbiology, 2023)
Methyl-branched aldehydes, especially 3-methylbutanal, has been reported to be perceived either as a malty or as a nutty/chocolate-like aroma, which were considered as an important flavor contributor in fermented meat products. Decomposition of leucine (Leu) by branched-chain amino acid transaminase (BACT) is a crucial step for the metabolism of Leu to 3-methylbutanal. This study was conducted to explore the effect of mixed starter culture (Lactobacillus fermentum YZU-06 and Staphylococcus saprophyticus CGMCC 3475) and addition of Leu (0, 1, and 3 mM) on the flavor and quality of fermented sausages. The pH, water activity, texture profile analysis, color, counts of lactic acid bacteria (LAB) and staphylococci, peptide and flavor compounds were detected during fermentation. The results showed that the starter culture group increased hardness, elasticity, the counts of LAB and staphylococci, peptide content, volatile flavor compounds as well as the sensorial scores of sausage, while decreased pH, aw, L* value and b* value compared to the non-inoculation group. The mixed starter of adding with 3 mM Leu enhanced the content of 3-methylbutanal and overall flavor of fermented sausages. In conclusion, it is applicable to directionally produce methyl-branched aldehydes and improve the overall quality of fermented sausage by the addition of Leu and using starter of L. fermentum YZU-06 and S. saprophyticus CGMCC 3475.